2021
DOI: 10.1088/1755-1315/756/1/012034
|View full text |Cite
|
Sign up to set email alerts
|

Weeds diversity in oil palm plantation at Segamat, Johor

Abstract: This research was conducted to study weeds composition and diversity with regards to management practices at three oil palm plantations in Segamat, Johor. Using nested quadrat sampling approach, a total of 19 families, 35 genera, 43 species and 4465 number of individuals of weeds species were found and recorded from the three plantations. The Shannon diversity index, H’ was 3.45 whereas the Evenness index, EH for the overall weeds species was 0.92. The highest weed diversity was observed at Kg. Sri Rahmat oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Dardona (2016) studied the floristic biodiversity in Gaza, Palestine. Ali et al (2021) studied the weeds composition and diversity with regards to management practices at palm plantations in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Dardona (2016) studied the floristic biodiversity in Gaza, Palestine. Ali et al (2021) studied the weeds composition and diversity with regards to management practices at palm plantations in Malaysia.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the land conversion problem, the expansion of oil palm also causes the widespread of weeds with some of them being invasive alien species. Studies have reported up to 60 species of plants categorized as weeds in oil palm plantations such as Asystasia gangetica, Clidemia hirta, Dyrnaria cordata, Imperata cylindrica, Trema cannabina, and Oxalis barrelieri (Ali et al 2021;Norlindawati et al 2019). While considered as a nuisance, weeds in oil palm plantations can serve as cover crops that provide various ecological functions, including reducing the speed of runoff water, preventing soil erosion and nitrogen leaching, improving soil organic matter, prohibiting the presence of other weeds through competition and reducing soilborne pathogens (Kanders et al 2017;Larkin et al 2015;Liu et al 2021;Wen et al 2017).…”
Section: Introductionmentioning
confidence: 99%